The Effectiveness of Audio-Visual Media in Enhancing Science Learning Students Outcomes at Elementary School 097 Palembang - Diana Lestari; Jayanti Jayanti; Ida Suryani (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
This study examines the impact of audio-visual learning media on students' academic performance in Integrated Science and Social Studies (IPAS), focusing on the subject of Indonesian cultural diversity. The study utilized a quantitative methodology, implementing a quasi-experimental design featuring a non-equivalent control group. The sample comprised 40 fourth-grade pupils from a primary school in Palembang, Indonesia, allocated into an experimental group and a control group. Data were gathered by pretest and post-test instruments consisting of multiple-choice questions and analysed using normality, homogeneity, and independent samples t-tests. The findings indicated that the experimental group attained a superior mean post-test score (M = 83.35) in contrast to the control group (M = 68.30). The hypothesis testing revealed a statistically significant difference (p < 0.05), indicating that audio-visual media substantially enhances students' learning results. These findings corroborate multimedia learning theory, indicating that the integration of visual and aural components improves cognitive processing and knowledge retention. The study suggests that audio-visual media serves as an excellent instructional tool for elementary education and advocates for its incorporation into classroom procedures.